PENGARUH ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KINERJA USAHA MEBEL - Hibatullah, Muhammad Faisol; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to identify the effects of entrepreneurial orientation andmarket orientation on the performance of furniture companies. The population of this studyis45furniture business owners in Bukir, an urban village in Pasuruan city. The data was harvestedthrough questionnaires and library research and was analyzed using multiple linear regressionin SPSS 26 for Windows. The research instruments were assessed using validitytest, reliability test, and classical assumption test. The hypothesis testing was performedusingFtest and t test, from which beta coefficient and relationship between variables were obtained. This study finds that entrepreneurial orientation (which consists of proactive, risk-taking, andanticipative indicators), market orientation (which consists of market information, customerorientation, and responsiveness) positively and significantly influence business performance.